ASSESSMENT OF EYE DROP INSTALLATION TECHNIQUE AMONG PATIENTS ATTENDING OUTPATIENT CLINIC AT PT. JLNGMC, CHAMBA - NEGI, SHALOO; KASHYAP, ADITYA; SHARMA, SMRITI (International Journal of Current Pharmaceutical Research, 2024)
Objective: A good eye drops installation technique and its knowledge is vital for curing eye ailments and preventing eye from harmful effects of over-dose and under-dose of drugs. The current study assessed the eye drop installation technique and corrected it by imparting them education regarding the same. Methods: A total of 120 patients were enrolled in the cross-sectional study using consecutive sampling technique till the sample size was achieved in a tertiary care hospital. The participants were observed by the trained observers for their steps of technique for installing eye drops and the errors were noted which were corrected by the observers and followed up till 3 visits to observe a change in the steps of technique. Results: The mean age of study participants was 41.44±15.4 y. Majority of them were in the age group 18-30 y (35%), females (55.8%), and belonging to upper middle socio-economic status (31.7%). Majority of study participants had 6/6 VA in right eye (65%) and left eye (61.7%). “Drop land on first attempt” and “direct bottle towards eyes” showed maximum improvement of 45.8% each followed by “tilt head while putting” showed 45 % improvement between 1st visit and 3rd visit. “Trouble putting drops” showed least improvement by 20% between 1st and 3rd visit. All the favorable ophthalmic practices showed a statically significant (<0.05) increase in their proportion in each visit. Conclusion: A high prevalence of errors while installing eye drops among participants were observed which were improved by educating them about right steps, as observe in follow up visits.